Kids at Work : Latinx Families Selling Food on the Streets of Los Angeles - Freedman, Russell, 1929-2018 (Book collections on Project MUSE., 1994)
This photo-essay describes child labor in the United States at the beginning of the century and how Lewis Hine fought for reforms. A profile of the investigative photographer & how he used his camera to expose the horrors of forced child labor in the United States during the early 20th century. His dramatic photos are included.